1968
DOI: 10.2134/agronj1968.00021962006000060013x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Forage Quality Comparisons of Sainfoin (Onobrychis viciaefolia Scop.) and Alfalfa (Medicago sativa L.)1

Abstract: We calculated seasonal accumulation of dry matter and crude protein in sainfoin and alfalfa and feed quality at three stages of maturity when species were grown on irrigated and dryland. Maximum accumulation of dry matter and crude protein occurred between 2 and 45% bloom for alfalfa and at 100% bloom for sainfoin on irrigated land. Dry matter and crude protein yield trends for both crops were similar on irrigated land and dryland. The maximum dry matter and crude protein contents for both sainfoin and alfalfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Ditterline and Cooper (1975) reported no failures in establishing sainfoin. However, persistence of sainfoin has often been reported as less than desirable (Carleton et al, 1968a; Ditterline and Cooper, 1975; Mowery and Matches, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ditterline and Cooper (1975) reported no failures in establishing sainfoin. However, persistence of sainfoin has often been reported as less than desirable (Carleton et al, 1968a; Ditterline and Cooper, 1975; Mowery and Matches, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Sainfoin is a perennial forage legume adapted to the calcareous soils of the western USA and can be used as an irrigated or dryland pasture species or for harvested forage. Forage quality of sainfoin compares favorably with alfalfa (Carleton et al, 1968a). Jensen et al (1968) reported that gains, feed consumption, feed efficiency, and digestibility were similar for beef cattle fed sainfoin or alfalfa hay.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Carleton et al (1968) reported that maximum accumulation of dry matter and protein occurred between 2 and 45% flower for alfalfa and at 100% flower for sainfoin. Compared to NRC (1984) guidelines, protein was above levels required for immature, mature, or lactating beef cattle.…”
Section: Forage Qualitymentioning
confidence: 99%